Representation of Political Identity in Billboard Advertisement: Linguistic Landscape Analysis in Kupang City - Benu, Naniana N.; Denil, Mauli; Prasetyo, Lery (English Education Study Program - Artha Wacana Christian University, 2024)
This study explores the political identity representation in billboard advertisements of the governor of NTT and the Mayor of Kupang candidates for the 2024-2029 period in Kupang City through the lens of linguistic landscape analysis. The research addresses three key aspects: the language employed in candidate billboards to shape political identity, the linguistic elements that reflect the candidates’ ideologies and political values, and the incorporation of local culture and languages to establish connections with the voters. Data was obtained using observation and documentation methods. Using qualitative analysis, this research reveals that the language and visual components of the billboards play a pivotal role in constructing the candidates' public personas, aligning political ideologies with the cultural and linguistic diversity of the region. The findings highlight the strategic use of local languages and cultural symbols, illustrating how these elements build rapport with voters and foster a sense of shared identity within the community.